PENGARUH EKSPEKTASI WISATAWAN, NILAI YANG DI RASAKAN, KEPUASAN WISATAWAN PADA PERILAKU WISATAWAN YANG BERTANGGUNG JAWAB TERHADAP LINGKUNGAN DAN LOYALITAS WISATAWAN DI KEMUNING SKY HILLS - Alfina Putri Pratama; Rini Kuswati (JURNAL LENTERA BISNIS, 2025)
This research seeks to examine the impact of tourist expectations, perceived value, and tourist satisfaction on environmentally responsible behavior and tourist loyalty at Kemuning Sky Hills. The study employed a purposive sampling method, involving 154 respondents in total. Data collection was conducted using a questionnaire designed with a Likert scale format. The data analysis in this research utilized Partial Least Squares (PLS) through the SMARTPLS 3.2 software. The PLS-SEM analysis consisted of two components: the outer model and the inner model. The findings revealed that tourist expectations significantly and positively influence perceived value, perceived value significantly and positively affects tourist satisfaction, tourist satisfaction significantly and positively impacts environmentally responsible behavior, and tourist satisfaction also significantly and positively influences tourist loyalty.